2014
DOI: 10.1186/s40657-014-0004-8
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in body mass and energy budget in Chinese bulbuls (pycnonotus sinensis)

Abstract: Background: Seasonal adjustments in body mass and energy budget are important for the survival of small birds in temperate zones. Seasonal changes in body mass, body temperature, gross energy intake (GEI), digestible energy intake (DEI), body fat content, as well as length and mass of the digestive tract, were measured in Chinese Bulbuls (Pycnonotus sinensis) caught in the wild at Wenzhou, China. Methods: Body mass was determined with a Sartorius balance. The caloric contents of the dried food and feces were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 65 publications
3
20
0
Order By: Relevance
“…The ability to adjust energy intake to compensate for the energy expended in thermogenesis is essential for survival (Hegemann et al, 2012). Environmental temperature and photoperiod can, however, alter birds' energy intake (Kendeigh, 1945;Stokkan et al, 1986;Lou et al, 2013;Wu et al, 2014b). We found that Chinese bulbuls in the CS group had the highest M b and that this was consistent with changes in GEI and DEI.…”
Section: Effects Of Temperature and Photoperiod On Morphology And Physupporting
confidence: 73%
See 3 more Smart Citations
“…The ability to adjust energy intake to compensate for the energy expended in thermogenesis is essential for survival (Hegemann et al, 2012). Environmental temperature and photoperiod can, however, alter birds' energy intake (Kendeigh, 1945;Stokkan et al, 1986;Lou et al, 2013;Wu et al, 2014b). We found that Chinese bulbuls in the CS group had the highest M b and that this was consistent with changes in GEI and DEI.…”
Section: Effects Of Temperature and Photoperiod On Morphology And Physupporting
confidence: 73%
“…Some small birds that live in seasonal environments increase their M b in winter (McKechnie, 2008;McKechnie and Swanson, 2010), by increasing their fat deposits and/or lean mass (Swanson, 1991a;Piersma et al, 1996). There is evidence to suggest that seasonal variation in the M b of Chinese bulbuls is due, at least in part, to seasonal variation in fat deposits and lean mass Wu et al, 2014a). Our results are consistent with those of previous reports on the response of Chinese bulbuls to seasonal change (Zheng et al, 2008a, and the M b of bulbuls was higher in cold groups than in warm groups, and in short photoperiod than in long photoperiod.…”
Section: Effects Of Temperature and Photoperiod On Morphology And Phymentioning
confidence: 99%
See 2 more Smart Citations
“…Phenotypic flexibility refers to phenotypic changes that are reversible, temporary and repeatable, such as acclimation and acclimatization (Piersma and Drent 2003;Starck 2009;Liknes and Swanson 2011). The study on phenotypic plasticity has become a central topic in evolutionary ecology and resident endothermic animals in temperate climates provide for natural experiments in phenotypic flexibility (Liknes and Swanson 2011;Wu et al 2014).…”
Section: Introductionmentioning
confidence: 99%